VOLUNTARY DISCLOSURE AND FIRM VALUE OF QUOTED CONGLOMERATES IN NIGERIA - Dilosi Dawn A.; Dr Egbe Solomon; Prof. Ogbonna Gabriel N. (American Journals, 2023)
This research work will be exploring how voluntary disclosure affects firm value of quoted conglomerates in Nigeria. In this research study, firm value was defined in terms of accounting policies and information on governance while firm value was measured using Tobin Q. This examination embraced an ex-post facto research design using secondary data of quoted conglomerates in Nigeria from 2012-2016, an aggregate of 3 conglomerates were incorporated into this study, the analysis were obtained using the ordinary least square method, descriptive statistics and also Pearson correlation coefficient. The outcomes demonstrated that voluntary disclosure has no huge association with firm value of conglomerates, it was concluded that voluntary disclosure is not sufficient to measure firm value of conglomerates i.e a rise in firm value of conglomerates is not necessarily determined by voluntary disclosure or a rise in voluntary disclosure would not necessitate an increase in firm value and it was also recommended that conglomerates should pay attention to other factors that would greatly affect either positively or negatively their value and help them maximize shareholders wealth.
Keywords: Voluntary Disclosure, Firm value, Accounting policies, Information on Governance, Tobin Q.